2009
DOI: 10.1364/oe.17.019166
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picosecond pulse generation by 40-GHz passively mode-locked quantum-dash 1-mm-long Fabry-Pérot laser diode

Abstract: Optical pulses at a repetition rate of 39.8 GHz have been observed in a dc-biased passively mode-locked quantum-dash Fabry-Pérot laser diode. The pulses generated by this diode are studied in the temporal and spectral domains using a second harmonic generation frequency-resolved optical gating system. By using a tunable band-pass filter, it is observed that the pulse width decreases as the number of lasing modes selected by the filter increases. Furthermore, by controlling the phase difference of the modes usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…A value of 860 fs was reported in the 1 MHz to 20 MHz range and an optimized RF linewidth of 30 kHz was also achieved at 242 mA with an estimated reduction in the timing jitter to 280 fs. These performance parameters were further improved by Latkowski et al [299] who successfully measured 720 fs pulse width from a 39.8 GHz Qdash mode-locked laser by passing through a 450 m single mode dispersion compensated fiber. Furthermore, as depicted in Fig.…”
Section: Self-pulsationmentioning
confidence: 99%
“…A value of 860 fs was reported in the 1 MHz to 20 MHz range and an optimized RF linewidth of 30 kHz was also achieved at 242 mA with an estimated reduction in the timing jitter to 280 fs. These performance parameters were further improved by Latkowski et al [299] who successfully measured 720 fs pulse width from a 39.8 GHz Qdash mode-locked laser by passing through a 450 m single mode dispersion compensated fiber. Furthermore, as depicted in Fig.…”
Section: Self-pulsationmentioning
confidence: 99%
“…This was carried out on a selfpulsating 30.3 GHz InAs/InGaAsP/InP QD-MLL. In terms of the timing jitter, Latkowski et al [82] utilized a 450-m long single mode dispersion-compensated fiber and demonstrated 720-fs wide pulses via a 39.8 GHz QD-MLL. Moreover, independently of the biasing current, a beating linewidth of 10e25 kHz was obtained with a timing jitter that varied from 350 to 150 fs while the peak power varied from 40 to 140 mW [83,84], as shown in Fig.…”
Section: Inas/inp Qdash Mode-locked Lasersmentioning
confidence: 99%
“…Oscilloscope traces are then analyzed to characterize the pulse shape. The result is shown in Fig.7(a) and it is clear that the pulse has a chirp profile that is not linear, mostly attributed to the material dispersion 28 . The pulse has FWHM of 3 ps with an asymmetric temporal shape which spans over 6.6ps at 6dB below the top of peak.…”
Section: Demonstration Of Chirp Compensationmentioning
confidence: 99%